2006
DOI: 10.1159/000092904
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Non-Glycosidase Activity of Invertebrate Destabilase-Lysozyme and of Its Helical Amphipathic Peptides

Abstract: Background: Since bactericidal properties of some lysozymes are independent of their glycosidase activity, we have investigated this phenomenon for destabilase-lysozyme (DL) from medicinal leech (Hirudo medicinalis). Methods: Glycosidase activity was determined on Micrococcus luteus, non-enzymatic antibacterial activity of heat-treated DL and of synthetic peptides α1, α2 and α3 (fragments of its primary structure) on M. luteus, Escherichia coli, Bacillus brevis and Streptomyces chrysomallus. Results: Glycosida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 11 publications
1
30
0
1
Order By: Relevance
“…Xue et al (2007) reported two i-type lysozymes in the eastern oyster, both of which signifi cantly inhibited the growth of E. coli, Vibrio vulnifi cus and Pediococcus cerevisiae, but at different concentrations. Zavalova et al (2006) detected high antimicrobial activity of heattreated destabilase/lysozyme that lacked glycosidase activity towards both Micrococcus luteus and E. coli. They considered this as evidence for a non-enzymatic antibacterial mode of action of the destabilase/lysozyme from medicinal leech besides its enzymatic activity.…”
Section: Antibacterial Activity Of Lysozymesmentioning
confidence: 99%
“…Xue et al (2007) reported two i-type lysozymes in the eastern oyster, both of which signifi cantly inhibited the growth of E. coli, Vibrio vulnifi cus and Pediococcus cerevisiae, but at different concentrations. Zavalova et al (2006) detected high antimicrobial activity of heattreated destabilase/lysozyme that lacked glycosidase activity towards both Micrococcus luteus and E. coli. They considered this as evidence for a non-enzymatic antibacterial mode of action of the destabilase/lysozyme from medicinal leech besides its enzymatic activity.…”
Section: Antibacterial Activity Of Lysozymesmentioning
confidence: 99%
“…Antifungal and antiprotozoal activities of lysozymes have also been reported and have been attributed to the hydrolysis of N-acetylglucosamine linkages in chitin that makes up the cell wall of fungus and some protozoa [3e5]. There is also increasing evidence that lysozymes kill Gram-positive and Gram-negative bacteria by nonenzymatic means [6,7]. While the antimicrobial activity of lysozymes has repeatedly been demonstrated in vitro, the contribution of lysozymes to host defences is only beginning to be unravelled in vivo [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Фермент Дест-Лиз (КФ 3.5.1.44), компонент секрета слюнных клеток медицинской пиявки, сначала был обнаружен и выделен как эндо-e-(g-Glu)-Lys-изопептидаза, расщепляющая эти связи в стабилизированном фибрине -основе кровяного тромба и в продукте его протеолиза -D-димере [1,2]. Позднее у этого фермента были выявлены лизоцимная и прямая антимикробная функции [3,4]. В результате экспрессии одного из трёх генов Дест-Лиз был получен и очищен его рекомбинантный вариант, которому свойственны все функции природной формы [5].…”
unclassified